Implementation of E-Government to Improve Public Transparency in the Provision of Integrated Services in Ciamis Regency - Hasan, Ratna; Agun Setiawan; Muhammad Raffi Kustiawan; Irfan Nursetiawan4 (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The problems found in this writing are related to the limited knowledge and technical skills of government employees in Ciamis Regency in operating and managing the new SPBE system. Facilities and infrastructure to support needed services are still limited to the implementation of an Electronic Based Government System (SPBE) in Ciamis Regency. This research aims to analyze the implementation of SPBE and its impact on transparency and service delivery ini Ciamis Regency. The research results show that the implementation of SPBE has succeeded in increasing information transparency and speeding up the process of providing services to the community in Ciamis. However, challenges such as uneven technological infrastructure and lack of digital literacy among employees are the main challenges. This research contributes to understanding the dynamics of SPBE implementation at the local level and its relevance in the context of strengthening good governance in indonesia.